2018
DOI: 10.1557/jmr.2018.363
|View full text |Cite
|
Sign up to set email alerts
|

Role of binders in solid electrolyte interphase formation in lithium ion batteries studied with hard X-ray photoelectron spectroscopy

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
(29 reference statements)
1
19
0
Order By: Relevance
“…11,14,[17][18][19] This one appears not only essential to constrain the volume expansion of the electrode or maintain contact with the current collector, but also to minimize the degradation of the liquid electrolyte by pre-forming an "artificial" protective SEI layer. 11,14,20,21 The preparation and processing of the electrode slurry (e.g. type of grinding, casting speed, drying temperature) and electrode parameters (porosity [22][23][24] and thickness 25 ) are also critical to the electrochemical behavior of the electrode.…”
Section: Introductionmentioning
confidence: 99%
“…11,14,[17][18][19] This one appears not only essential to constrain the volume expansion of the electrode or maintain contact with the current collector, but also to minimize the degradation of the liquid electrolyte by pre-forming an "artificial" protective SEI layer. 11,14,20,21 The preparation and processing of the electrode slurry (e.g. type of grinding, casting speed, drying temperature) and electrode parameters (porosity [22][23][24] and thickness 25 ) are also critical to the electrochemical behavior of the electrode.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to the question of how the addition of an insulating polymeric binder, added to mitigate the effect of Si expansion in composite slurries, affects the SEI formation. We know that the binder has a role in electrochemistry regardless of the anode. , For example, the commonly used binder PVDF does not work in silicon-based chemistries, but the use of poly­(acrylic acid) (PAA) does. In addition, the components of composite-based electrodes can change the SEI. Indeed, one study looking at different surface area carbons, the choice of PAA, and CMC binders led to an “artificial SEI” that enhanced the cyclability .…”
Section: Introductionmentioning
confidence: 99%
“…Preferential solvent reduction on the basal plane at lower potential vs. Li + /Li determines larger organic content in the SEI 1 . Besides, the SEI growth and structure depend on binder material 23,24 . To the best of our knowledge, only two in situ AFM measurement of SEI formation were reported on a composite electrode comprised of graphite powder mixed with polyvinylidene difluoride (PVDF) binder and a conductive additive: (1) in 1997 25 authors reported difficulties of such measurements, and (2) in 2017 26 the imaging quality was not enough to observe SEI formation due to rough surface and AFM tip contamination.…”
mentioning
confidence: 99%